Hubungan Antara Tingkat Pengetahuan Ibu Dengan Pemilihan Kontrasepsi Di PMB Winastuty - Indriyani Indriyani (Pusat Riset dan Inovasi Nasional, 2024)
From the data at PMB Winastuty, Jetaksari village in 2022, there were several IUD acceptors (10) participants, MOW acceptors (2) participants, MOP acceptors (0) participants, implant acceptors (150) participants, injection acceptors (1,275) participants, pill acceptors (24) participants, and condom acceptors (0) participants. Moreover, most of them do not know what hormonal and non-hormonal contraception is and do not know about the contraceptive methods they use in terms of how to use contraception, the advantages and disadvantages of contraception, contraceptive indications, contraceptive contraindications, the time of use of contraception, side effects, and treatment with contraception. All they know is how to delay pregnancy so that it is not too close and at a low cost. To determine the relationship between the level of knowledge of the mother and the choice of contraception at PMB Winastuty in Jetaksari Village, Sayung District, Demak Regency, Central Java. This research is a quantitative correlation study using a cross-sectional approach and a purposive sampling method. In this study, all family planning acceptors who visited PMB Winastuty in 2022 totalled 1,461 acceptors. The average was made of 1,461 ÷ 12 = 121.75 per month, and it was rounded up to 122 acceptors each month, following the object under study, all hormonal and non-hormonal acceptors who visited PMB Winastuty. The sampling method in this study was purposive sampling with a total of 94 family planning acceptors. Data collection techniques used primary data collected through questionnaires and bivariate analysis using the Mann-Whitney test. Based on data analysis, the Asymp value was obtained. Sig 0.426 > 0.05. These results indicate that there is no relationship between the level of knowledge of the mother and the choice of contraceptive method.